2010
DOI: 10.1152/ajpheart.00181.2010
|View full text |Cite
|
Sign up to set email alerts
|

Both A2a and A2b adenosine receptors at reperfusion are necessary to reduce infarct size in mouse hearts

Abstract: Pre- and postconditioning depend on the activation of adenosine receptors (ARs) at the end of the index ischemia. The aim of this study was to determine which receptor subtypes must be activated. In situ mouse hearts underwent 30 min of regional ischemia, followed by 2 h of reperfusion. As expected, either ischemic postconditioning (6 cycles of 10 s of reperfusion and 10 s of coronary occlusion) or infusion of the selective A(2b) adenosine receptor (A(2b)AR) agonist BAY60-6583 (BAY60) for 60 min, starting 5 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 21 publications
1
42
1
1
Order By: Relevance
“…Much less is known about the role of A 2B receptors in myocardial ischemia-reperfusion injury, although there are reports (17,28,42) showing that A 2B receptor stimulation during reperfusion is cardioprotective. As stated above, our previous reports (19,33) demonstrating that ZM-241385 blocked A 1 cardioprotection could have been the result of antagonism of A 2B receptors due to the high affinity of this antagonist for A 2B receptors (1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Much less is known about the role of A 2B receptors in myocardial ischemia-reperfusion injury, although there are reports (17,28,42) showing that A 2B receptor stimulation during reperfusion is cardioprotective. As stated above, our previous reports (19,33) demonstrating that ZM-241385 blocked A 1 cardioprotection could have been the result of antagonism of A 2B receptors due to the high affinity of this antagonist for A 2B receptors (1).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of A 1 and A 3 receptors before ischemia is cardioprotective (2,19,20,24,30,33,37,38,41), whereas A 2A and A 2B receptors appear to exert their effects during reperfusion (10,13,17,18,28,34,42,43). Adenosine A 3 receptor activation during reperfusion has been reported to be cardioprotective (8), but there are conflicting reports on whether A 1 receptor activation during reperfusion is beneficial (3,7,30,39,40).…”
mentioning
confidence: 99%
“…Evidence that activation of both A 1 and A 2 receptors during hypoxia can attenuate myocardial injury was claimed (Stambaugh et al, 1997;Tracey et al, 1997;Liang and Jacobson, 1998). Endogenous adenosine makes a significant contribution to A 1 agonistmediated prevention of necrosis in a cardiac cell model of ischemia by cooperative interactions with both A 2A and A 2B receptors, but does not play a role in A 3 agonistmediated protection (Urmaliya et al, 2009;Methner et al, 2010). It was reported that A 1 and A 3 receptor agonists reduce hypoxic injury through the involvement of p38 MAPK (Leshem-Lev et al, 2010).…”
Section: Ischemiamentioning
confidence: 99%
“…It has been claimed that A2AR and A2BR act in concert to induce strong protection against reperfusion injury in rat hearts [549] and co-operative activation of A1R and A2AR to produce cardioprotection in ischaemiareperfused mouse heart has also been reported [550]. Indeed, endogenous adenosine makes a significant contribution to A1R agonist-mediated prevention of necrosis in a cardiac cell model of ischaemia by co-operative interactions with both A2AR and A2BR, but does not play a role in A3R agonistmediated protection [551,552]. Figure 7 shows a simplified depiction of the impact of adenosine receptors in protecting against myocardial injury following ischaemia or hypoxia.…”
Section: Ischaemiamentioning
confidence: 99%